A view from comparative tax law: Cryptocurrencies, transactions and taxable events. Tax treatment in Peru, problems and recommendations - Durán Rojo, Luis (2021)
Currently, we are facing a significant increase in transactions with cryptocurrencies as an alternative to the traditional payment system, and even as an investment; so, most countries in the world have already taken action on the tax treatment of these transactions: There are various pronouncements issued by the tax authorities in the world and, in some jurisdictions, specific legislative measures have been adopted to regulate the tax effects of transactions with cryptocurrencies. For that reason, it is necessary to evaluate the current tax treatment of activities with cryptocurrencies in Peruvian legislation, in order to identify -from a comparative perspective- the main tax problems and to provide some guidelines to be taken into account for an eventual regulation.